Anisotropic magnetoresistance in Sr2FeMoO6 thin films - Nykänen, Akseli; Angervo, Ilari; Huhtinen, Hannu; Paturi, Petriina (IOP Publishing, 2026)
Epitaxial Sr2FeMoO6films were investigated for their magnetoresistive properties. The results revealed a distinct anisotropic resistance response to the magnetic field, which was especially noticeable when the current path was oriented along different crystallographic directions. This anisotropic behavior was observed as varying symmetries in the resistance-field direction dependence. The phenomenon was discussed in the context of magnetocrystalline anisotropy as well as more general electrical properties. The findings suggest that some commonly accepted explanations for anisotropic magnetoresistance are insufficient to account for the recent observations. A deeper understanding of the electrical properties of Sr2FeMoO6-and similar materials-is therefore necessary. Additionally, the work demonstrated an enhancement in magnetic properties as a result of temperature annealing treatment.